Activating the internal control system to improve administrative performance and reduce fraud in small industrial establishments: a case study of blocks and ready-mix concrete factories in Bani Malik, Asir region for the academic year (1443 AH-1444 AH) - Asiri, Hanadi Adbulhadi; Alsayed, Huda Ebrahim (Journal of Economic, Administrative and Legal Sciences, 2022)
The main goal of this study is to know the role of activating Internal control to improve administrative performance and reduce fraud in small business industries. In this paper, we use Descriptive analytical method, and it includes 12 factories of ready-made Block and concrete in (Bani Malek Asir region). The results of this study show that 1-internal control is a part of the industries activity, and it’s part of the system they use in organizing their operations.2-The outlay that borne by industrial companies because of heavy equipment consumption are not specified. Our recommendation for this studyare,1-to improve and strengthen the internal control system in industries, in order to reduce manipulation and fraud. 2-Furthermore, it’s important for internal auditors to be independence,3- and to follow effective procedures in evaluation the internal audit activity in periodically manor.